The process communications - Medcom Trainex (Cypress, CA : Medcom Trainex, 1984)
This program explores the goals and the components of effective communication. It describes six-step communication process and discusses impediments to communication. It also demonstrates techniques for speaking and listening effectively
Primary consultant: Phyllis S. Brenner ; contributing consultant: Suzanne G. Wilson
Keywords: Communications; Nursing, Practical